DAMPAK GLOBALISASI TERHADAP SISTEM PENDIDIKAN: PERSPEKTIF SOSIOLOGI PENDIDIKAN - Hasan Basri (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
From the perspective of the sociology of education, this magazine examines how globalization has affected the education system. Many aspects of human existence have been affected by globalization, including the education system. Through the rapid exchange of information and technical advances, globalization has made the world more interconnected. Globalization has created new opportunities and difficulties for education. The influence of globalization on the education system. One result is the requirement to create curricula that are more inclusive and relevant to the world as a whole. To equip students to become capable global citizens, education systems must adapt to changing global demands. In addition, the movement of students and teachers is affected by globalization.This phenomenon affects socio-economic inequality within a country as well as the educational gap between industrialized countries and developing countries. Inequality in access to technology, resources, and educational opportunities is a barrier to reducing this gap. In this study, literature is used as a research method. Globalization has led to many cultural exchanges on a global scale. In an educational context, this can result in diversification in curriculum, instruction and assessment